ELECTROCARDIOGRAM IN CHRONIC COR PULMONALE - ZUCKERMANN, R; PALLARES, ES; FISH LEDER, BL; CABRERA, ENRIQUE (INSTITUTO DE CARDIOLOGIA, CD. MEXICO, DF, MEX, 1948)
After the study of the electrocardiograms of fifty cases of chronic cor pulmonale, we consider that the principal diagnostic signs (see Fig. 11) are: (1) high and peaked P waves with prominent auricular T waves in Leads II, III, and VF; (2) negative P wav
AM HEART J
Keywords: ELECTROCARDIOGRAM, CHRONIC, PULMONALE; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA